THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION, PRODUCT KNOWLEDGE, AND FINANCIAL LITERACY ON BUSINESS PERFORMANCE IMPROVEMENT WITH PRODUCT INNOVATION CAPABILITY AS AN INTERVENING VARIABLE - Istighfariani, Nadya; Ferdinand, Augusty Tae; Arif, Abdul Rahman (The International Journal of Business Review (The Jobs Review), 2024)
Purpose— This study aims to examine how entrepreneurial orientation, product knowledge, and financial literacy impact the business performance of food MSMEs in Pantai Indah Kapuk (PIK), with product innovation capability acting as an intervening factor.Design/methods/approach –  A quantitative survey was conducted with 96 MSME owners in PIK using structured questionnaires. Data analysis was performed using Structural Equation Modeling (SEM) with Smart-PLS software to test variable relationships.Findings – The study finds that entrepreneurial orientation positively impacts product innovation capability, which in turn boosts business performance. Product knowledge also enhances product innovation, while financial literacy directly improves business performance by enabling better financial management. Research implications/limitations—   This study suggests that improving entrepreneurial orientation, product knowledge, and financial literacy through training can boost MSME performance. However, its findings are limited to MSMEs in PIK and may not be applicable elsewhere, with self-reported data possibly introducing bias.Originality/value – This research offers valuable insights into the combined effects of entrepreneurial orientation, product knowledge, and financial literacy on MSME performance, highlighting the role of product innovation in business success, particularly in competitive markets like the food industry.